Translation-invariant p-adic quasi-Gibbs measures for the Ising–Vannimenus model on a Cayley tree - Mukhamedov, Farrukh; Saburov, Mansoor; Khakimov, Otabek (Maik Nauka Publishing / Springer SBM, 2016)
We consider the p-adic Ising–Vannimenus model on the Cayley tree of order k = 2. This model contains nearest-neighbor and next-nearest-neighbor interactions. We investigate the model using a new approach based on measure theory (in the p-adic sense) and describe all translation-invariant p-adic quasi-Gibbs measures associated with the model. As a consequence, we can prove that a phase transition exists in the model. Here, “phase transition” means that there exist at least two nontrivial p-adic quasi-Gibbs measures such that one is bounded and the other is unbounded. The methods used are inapplicable in the real case. © 2016, Pleiades Publishing, Ltd.